A framework for innovative service design. Issue 9 (26th July 2016) - Furrer, Olivier; Sudharshan, D.; Tsiotsou, Rodoula H.; Liu, Ben S.
ABSTRACT: Drawing on research from design science, marketing, and service science, our paper provides an integrated framework for evaluating and directing innovative service design. The main goal of our review is to highlight the strengths of existing frameworks and to suggest how they can be enhanced in combination with design science principles. Based on our review, we propose a new framework for the design of innovative services that integrates several key paradigmatic approaches and identifies fundamental open research questions. Our approach is unique as it combines three service disciplines, namely services marketing, service science, and design science, and provides a new framework that describes step by step the procedure that needs to be taken and the conditions that need to be met for developing innovative services. We believe that providing such a framework is a valuable addition to the literature.